Terceirização da colheita de soja como alternativa para redução de custos totais de produção - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Currently, the soybean (Glycine Max) is considered a cultivation of worldwide importance since it is used in the agroindustry and, in addition, it is the main Brazil’s agricultural product. The Brazilian production system has faced rising production costs in recent years, which may cause a reduction in profitability. The cost of acquiring and maintaining machinery and equipment is one of those that showed a significant increase, and this increase is also reflected in the sale price of the soybean. Thus, the present Graduation Completion Research aims do analyze whether the outsourcing of soybean harvesting can be considered a factor in reducing production costs. To achieve this, a comparison is made between the traditional method of mechanized harvesting, with its own harvester, and the use of an outsourced harvesting service by calculating the fixed and variable costs of maintaining its own machinery to perform the service. As a result, it is concluded that hiring an outsourced company reduces production costs by 17%, showing off that the outsourcing of agricultural services, something regulated by national laws, can emerge as an interesting alternative for rural producers seeking to reduce the production total cost.
Outsourcing soybean harvesting as an alternative to reduce total production costs
Keywords: Terceirização; Máquinas; Custos de produção; Outsourcing; Machines; Production costs; CNPQ::CIENCIAS AGRARIAS